2016
DOI: 10.1002/2015wr018364
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among hydraulic conductivity distributions, subsurface topography, and transport thresholds revealed by a multitracer hillslope irrigation experiment

Abstract: Interactions among hydraulic conductivity distributions, subsurface topography, and lateral flow are poorly understood. We applied 407 mm of water and a suite of tracers over 51 h to a 12 by 16.5 m forested hillslope segment to determine interflow thresholds, preferential pathway pore velocities, largescale conductivities, the time series of event water fractions, and the fate of dissolved nutrients. The 12% hillslope featured loamy sand A and E horizons overlying a sandy clay loam Bt at 1.25 m average depth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 71 publications
6
54
0
Order By: Relevance
“…However, model calibrations on lateral subsurface flow and δ 2 H showed that higher bypass values produced better simulations (not shown); this is in contrast to McGuire et al (2007) who found that smaller bypass values produced better simulations. Our finding though is consistent with dye-staining experiments at a nearby site (McGuire et al, 2007), other studies at this site (McGuire and McDonnell, 2010;van Verseveld et al, 2008) and observations published in other studies (Radulovich et al, 1992;Hornberger et al, 1990;van Stiphout et al, 1987;Jackson et al, 2016) that all showed the importance of bypass flow. Additionally, our finding is in agreement with higher observed average vertical velocity at well E04 compared to the deep lysimeters during the sprinkler experiment.…”
Section: Process Understanding Through the Hillvi Modelsupporting
confidence: 82%
See 2 more Smart Citations
“…However, model calibrations on lateral subsurface flow and δ 2 H showed that higher bypass values produced better simulations (not shown); this is in contrast to McGuire et al (2007) who found that smaller bypass values produced better simulations. Our finding though is consistent with dye-staining experiments at a nearby site (McGuire et al, 2007), other studies at this site (McGuire and McDonnell, 2010;van Verseveld et al, 2008) and observations published in other studies (Radulovich et al, 1992;Hornberger et al, 1990;van Stiphout et al, 1987;Jackson et al, 2016) that all showed the importance of bypass flow. Additionally, our finding is in agreement with higher observed average vertical velocity at well E04 compared to the deep lysimeters during the sprinkler experiment.…”
Section: Process Understanding Through the Hillvi Modelsupporting
confidence: 82%
“…They attributed this to the advancement of a pressure wave instead of advective flow of new water. Following recommencement of irrigation, Jackson et al (2016) observed during their multi-tracer hillslope irrigation experiment a fast trench flow and piezometer response indicating a pressure wave celerity much faster than observed dye tracer velocities. Rasmussen et al (2000) presented parametric expressions for the celerity, which predicted pressure wave travel times 2 to 15 times faster than the tracer velocity for their short-duration fluid irrigation experiments with intact saprolite columns.…”
Section: Celerities and Velocities At The Hillslope Scalementioning
confidence: 99%
See 1 more Smart Citation
“…The 19.8‐m travel distance estimated for the Czech hillslope studied, for example, by Dusek and Vogel () closely matched the 25‐m contributing length estimated from their experimental work. Similarly, Jackson et al () also found that the contributing length estimated from the water balance for a plot‐scale irrigation experiment also closely matched the estimated DTD within the R watershed at the Savannah River Site. Irrigating a hillslope underlain by a fractured and leaky fragipan, Parlange et al () found that the effective contributing area was much smaller than the irrigated area.…”
Section: Calculated Downslope Travel Distances In Different Landscapementioning
confidence: 60%
“…We were also unable to use studies that reported large ranges of conductivities for each layer, but no central tendency. Hydraulic conductivities of surface soils and nearsurface impeding layers can range over several orders of magnitude (e.g., Jackson et al, 2016), and therefore, ranges of hydraulic conductivities without central tendencies could not be used to estimate DTD. 10.1029/2018WR022920 Detty and McGuire (2010).…”
Section: Water Resources Researchmentioning
confidence: 99%